Developing a Teaching Plan for The Third Listening Semester Using The Common European Framework of Reference for Languages Through Blended Learning - Riziq Fitra Pratama; Muhammad Kamal bin Abdul Hakim; Syamsi Setiadi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The scientific study was conducted in Arabic Language Study Program, Faculty of Languages and Arts, Jakarta State University, this study aims to produce development of RPS Istima’ 3 (third listening) used by CEFR based on blended learning. The method used in this study is the development of ADDIE Model (Analysis, Design, Development, Implementation and Evaluation) developed by Dick and Carey. Which researcher limited the step to as follows: (1) Analysis; the need analysis of Arabic Language Study Program lecturers and students in Listening Course 3 CEFR-based Semester Lesson Plan through Blended Learning, (2) Design and Development; the researcher collected the listening course material of B-1 level based on CEFR which applied Blended Learning in teaching method and on previous Semester Lesson Plan, (3) Product’s assessment was done by experts. The results show that the students’ need analysis on CEFR-based Semester Lesson Plan of Listening Course 3 through Blended Learning scored at 2,46 in average which categorized ‘very needed’. Furthermore, the expert review of the lesson plan gained 4 for its average which then defined as ‘very good’ category. Thus, CEFR-based Semester Lesson Plan of Listening Course 3 through Blended Learning is well worth using in Istima’ 3 teaching and learning activities in Jakarta State University.